Impacto dos atropelamentos sobre a herpetofauna da Floresta Atlântica (PR-340, Antonina, Paraná) - Silva, Mitzi Oliveira da; Oliveira, Igor Soares de; Cardoso, Manoela Woitovicz; Graf, Vinalto (Acta Biológica Paranaense, 2007)
Impacto dos atropelamentos sobre a herpetofauna da Floresta Atlântica (PR-340, Antonina, Paraná) & Vinalto Graf